Progress in Rehabilitation Treatments for Sepsis Patients in ICU - Wang Ling; Zhang Zhen (Journal of Human Health Research, 2022)
Early active mobilisation and rehabilitation in the intensive care unit (ICU) is being used to prevent the long-term functional consequences of critical illness, sepsis patients need early rehabilitation treatment. Individualized rehabilitation is a safe and effective approach for patients with sepsis. This review aimed to introduce the necessity of rehabilitation for patients with sepsis in the ICU, the composition of the rehabilitation team, the time to begin rehabilitation, the focus of rehabilitation, and the main approaches.
Keywords: Sepsis